High prevalence of idiopathic (islet antibody‐negative) type 1 diabetes among Indian children and adolescents. Issue 1 (29th July 2020) - Vipin, Valam Puthussery; Zaidi, Ghazala; Watson, Kelly; G Colman, Peter; Prakash, Swayam; Agrawal, Suraksha; Bhatia, Vijayalakshmi; Dabadghao, Preeti; Bhatia, Eesh
Abstract: Objectives: To study the prevalence and clinical characteristics of islet antibody‐negative (idiopathic) type 1 diabetes mellitus (T1DM) among Indian children and adolescents at the time of diagnosis of illness. Methods: In a hospital‐based cross‐sectional study, we studied 110 patients with T1DM aged ≤18 years. This included 61 patients with duration of diabetes ≤2 weeks (mean ± SD age of onset 9.9 ± 4.4 years) and 49 patients with duration 2 to 12 weeks. Antibodies against GAD65 (GADA), IA‐2 (IA‐2A) and zinc transporter 8 (ZnT8A), detected by radio‐binding assay, were measured in all patients. Insulin autoantibody (IAA) was measured only in subjects with duration ≤2 weeks, using a competitive radio‐binding assay. Results: The prevalence of GADA, IA‐2A, and ZnT8A was 53%, 34%, and 29% respectively, while IAA (measured in 61 patients) was detected in 31%. All four antibodies were absent in 17 of 61 (28%) patients. The prevalence of islet antibody‐negative patients was similar among both sexes and in children with onset younger and older than 10 years. ZnT8A was the only antibody detected in four patients, and its measurement resulted in 6% reduction in islet antibody‐negative patients. Patients with idiopathic T1DM did not differ in their clinical features or fasting plasma C‐peptide at the onset and after follow‐up of 1 year. Compared with idiopathic T1DM, antibody‐positive patients had an increased allele frequency of HLA DRB1*0301 (46% vs 14%, OR = 5.10 [confidence interval = 1.61‐16.16], P = .003). Conclusion: Nearly 30% of Indian patients were negative for all islet antibodies at the onset of T1DM. Patients with idiopathic T1DM had similar clinical features to antibody‐positive subjects.